1981
DOI: 10.1007/bf02402836
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of the strength of pseudo-binary platinum-based L12 alloys with B-subgroup elements

Abstract: The notable effect of atomic radius ratio of the components of L12-0rdered alloys on the temperature dependence of their strength has been demonstrated using suitable alloys and alloying elements. Pt3 In and Pt3Sn were chosen and partial substitutions were made of the minor components with Ga and TI, and with Ge and Pb, respectively, keeping the electron concentration of the system constant. The positive temperature dependence was generally found to be strengthened by the smaller substituting atoms and to be w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In general, substitution of ternary elements away from the stoichiometric composition reduces the composition region in which the L1 2 structure is stable by reducing the average electron atom ratio or increasing the atomic radius ratio. 5,3942 The effects of compositional deviations from stoichiometry 32,43 and ternary additions 4446 also fit the predicted behaviour of this concept.
8 The crystal structure of L1 2 (left), and D0 22 (right)
…”
Section: Anomalous Yield In Intermetallic L12 Alloyssupporting
confidence: 58%
“…In general, substitution of ternary elements away from the stoichiometric composition reduces the composition region in which the L1 2 structure is stable by reducing the average electron atom ratio or increasing the atomic radius ratio. 5,3942 The effects of compositional deviations from stoichiometry 32,43 and ternary additions 4446 also fit the predicted behaviour of this concept.
8 The crystal structure of L1 2 (left), and D0 22 (right)
…”
Section: Anomalous Yield In Intermetallic L12 Alloyssupporting
confidence: 58%
“…It was shown that among nickel base A3B compounds with B as one of transition elements, the structures of Ni3Ti, Ni3Zr and Ni3Hf themselves can not be L12(cT) but are the D024(chT) and that as the minority component of each compound changes from (Ti, Zr, Hf) to (V, Nb, Ta), the structures involving R component such as D022(cR) or D019(hR) appear (30) This would by itself predict that in Ni3Al, the addition of these transition metal elements results in reducing the stability of its cT structure and thereby enhancing the mechanical anomaly. With platinum based A3B compounds, a better illustration is possible.…”
Section: The Magnitude Of the Positive Temperature Dependence Of Strementioning
confidence: 99%
“…Oya et al [7] reported that the four L1 2 compounds, Ni 3 Al, Ni 3 Ga, Ni 3 Ge, and Ni 3 Si, form a tetrahedron of continuous solid solution in a temperature range of 900 -1000 8C, which means that these four L1 2 compounds are completely miscible. Suzuki et al [8,9] showed a continuous solid solution formation between Ni 3 Ge and Fe 3 Ge. The existence of the continuous solid solutions Cu 3 Au -Cu 3 Pd and Cu 3 Au -Cu 3 Pt was demonstrated by Nakahigashi et al [10].…”
Section: Introductionmentioning
confidence: 98%